Peran Kecerdasan Buatan dalam Menghadapi Tantangan Pendidikan Masa Depan - Sefrin Siang Tangkearung; Daud Rodi Palimbong; Sarah Maramba' (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2024)
This research is very important in order to face future educational challenges, an integrated approach between humans and artificial intelligence is very necessary. Artificial intelligence can be a very useful tool for educators, students and school administrators to achieve better and relevant educational goals in today's times. This research aims to describe the role of artificial intelligence in facing future educational challenges. The type of research used in this research is descriptive qualitative research. The subjects in this research were teachers, school principals and students. The data collection techniques used in this research are observation, interviews and documentation. The results of this research include the ability of artificial intelligence to process large data quickly and extract complex patterns, artificial intelligence makes a significant contribution in various aspects of education, from personalizing learning to increasing the efficiency of school administration, accommodating students' individual needs through personalizing learning, adapting the curriculum and learning methods according to the needs and learning speed of each student. enabling educators to provide more relevant and effective learning experiences, increase student motivation, and reduce gaps in academic achievement. Not only in the classroom, artificial intelligence also plays a role in simplifying administrative tasks for educators and school staff. By automating processes such as scheduling, student data management, and performance evaluation, artificial intelligence reduces administrative workload, allowing educators to focus more on direct interactions with students and curriculum development. Overall, artificial intelligence has a promising role to play in facing future educational challenges. With thoughtful application and responsiveness to relevant issues, AI can become a powerful tool to improve the quality of education, preparing future generations to face the demands of an increasingly complex society and job market.